(untitled) (Medico Legal Update, 2020)
The knowledge on prevention of Carcinoma Cervix among the reproductive age group women in Kokilamedu village at Kanchipuram District, Tamil Nadu, India. The objectives were to assess the knowledge on prevention of Carcinoma Cervix among women in Kokilamedu village at Kanchipuram District, Tamil Nadu and to find out the association between the level of knowledge with demographic variables. The convenience sampling was used to select 104 samples of reproductive age group women. The data collection tools were validated and reliability was established. The data were collected by self administered questionnaire. The collected data was tabulated and analyzed. Descriptive and inferential statistics method were used. The study shows that 45% of the women had poor knowledge, 59% of the mothers had moderate knowledge and non of the women had adequate knowledge regarding prevention of Carcinoma Cervix. There was no significant association between the knowledge and the selected Demographic Variables.